1-FFT amino acids involved in high DP inulin accumulation in Viguiera discolor - De Sadeleer, Emerik; Struyf, Tom; Vergauwen, Rudy; Le Roy, Katrien; Van den Ende, Wim (Frontiers in Plant Science, 2015)
Fructans are important vacuolar reserve carbohydrates with drought, cold, ROS and general abiotic stress mediating properties. They occur in 15% of all flowering plants and are believed to display health benefits as a prebiotic and dietary fiber. Fructans are synthesized by specific fruc- tosyltransferases and classified based on the linkage type between fructosyl units. Inulins, one of these fructan types with β(2-1) linkages, are elongated by fructan:fructan 1-fructosyltransferases (1-FFT) using a fructosyl unit from a donor inulin to elongate the acceptor inulin molecule. The sequence identity of the 1-FFT of Viguiera discolor (Vd) and Helianthus tuberosus (Ht) is 91% although these enzymes produce distinct fructans. The Vd 1-FFT produces high degree of poly- merization (DP) inulins by preferring the elongation of long chain inulins, in contrast to the Ht 1-FFT which prefers small molecules (DP3 or 4) as acceptor. Since higher DP inulins have in- teresting properties for industrial, food and medical applications, we report here on the influence of two amino acids on the high DP inulin production capacity of the Vd 1-FFT. Introducing the M19F and H308T mutations in the active site of the Vd 1-FFT greatly reduces its capacity to pro- duce high DP inulin molecules. Both amino acids can be considered important to this capacity, although the double mutation had a much higher impact than the single mutations.